Evaluating feedback interventions to improve healthcare worker hand hygiene adherence using an automated hand hygiene monitoring system - James P. Steinberg; Ashley A. Tippett; Victoria L. Walsh; Puja Y. Shah; Kirk A. Easley; Neeta V. Shenvi; John M. Boyce; Radhika Prakash-Asrani; Jesse T. Jacob (Infection Control & Hospital Epidemiology, 2026)
Abstract Background: Automated hand hygiene monitoring systems (AHHMSs) can monitor a large number of hand hygiene opportunities, and some provide real-time feedback; however, the impact of these systems is unclear. We sought to better understand how one of these systems improves hand hygiene adherence. Methods: The AHHMS was installed in seven units of an urban teaching hospital, and healthcare workers, primarily nurses and nurse technicians, were enrolled. We used a prospective observational cohort design with multiple interventions, including providing individual adherence rates and real-time voice reminders, to understand how these interventions improve hand hygiene adherence. Results: Over the 40-week study period, 744,769 hand hygiene observations were observed among the 346 participants. The overall hand hygiene adherence rate increased from 37.0% (95% CI: 34.3% to 39.9%) at the start of the study to 55.5% (95% CI: 51.6% to 59.6%). This increase of 18.5% was statistically significant. However, adherence varied widely among different units and between individual participants. Voice reminders (58.7% (95% CI: 55.9% to 61.6%)) led to a significantly higher hand hygiene adherence rate than weekly individual feedback (46.4% (95%: 42.2% to 51.0%)) after adjusting for work shift and the seven individual participating clinical units. With the combination of interventions, improved adjusted adherence rates were sustained until the end of the study period. Conclusions: After the introduction of the AHHMS, real-time voice reminders improved short-term hand hygiene adherence more than feedback of individual adherence rates. Multiple interventions and cultural changes are required to sustain improved adherence.